In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

Chemical composition of young stars in the leading arm of the Magellanic system - Zhang, Lan; Moni Bidin, Christian; Casetti-Dinescu, Dana I.; Méndez, Réne A.; Girard, Terrence M.; Korchagin, Vladimir I.; Vieira, Katherine; van Altena, William F.; Zhao, Gang (The Astrophysical Journal, 2017)
Chemical abundances of eight O- and B-type stars are determined from high-resolution spectra obtained with the MIKE instrument on the Magellan 6.5 m Clay telescope. The sample is selected from 42 candidates for membership in the Leading Arm (LA) of the Magellanic System. Stellar parameters are measured by two independent grids of model atmospheres and analysis procedures, confirming the consistency of the stellar parameter results. Abundances of seven elements (He, C, N, O, Mg, Si, and S) are determined for the stars, as are their radial velocities and estimates of distances and ages. Among the seven B-type stars analyzed, the five that have radial velocities compatible with membership of the LA have an average [Mg/H] of -0.42 ±0.16, significantly lower than the average of the remaining two, [Mg/H] = -0.07 ±0.06, which are kinematical members of the Galactic disk. Among the five LA members, four have individual [Mg/H] abundance compatible with that in the LMC. Within errors, we cannot exclude the possibility that one of these stars has an [Mg/H] consistent with the more metal-poor, SMC-like material. The remaining fifth star has an [Mg/H] close to Milky Way values. Distances to the LA members indicate that they are at the edge of the Galactic disk, while ages are of the order of ∼50-70 Myr, lower than the dynamical age of the LA, suggesting a single star-forming episode in the LA. V LSR of the LA members decreases with decreasing Magellanic longitude, confirming the results of previous LA gas studies. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy

The Origins of Young Stars in the Direction of the Leading Arm of the Magellanic Stream: Abundances, Kinematics, and Orbits. - Zhang, Lan; Casetti-Dinescu, Dana I; Bidin, Christian Moni; Mendez, Rene A; Girard, Terrence M; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F; Zhao, Gang (The Astrophysical journal, 2019)
We explore the origins of the young B-type stars found by Casetti-Dinescu et al. (2014) at the outskirts of the Milky-Way disk in the sky region of Leading Arm of the Magellanic Stream. High-resolution spectroscopic observations made with the MIKE instrument on the Magellan Clay 6.5m telescope for nine stars are added to the previous sample analyzed by Zhang et al. (2017). We compile a sample of fifteen young stars with well-determined stellar types, ages, abundances and kinematics. With proper motions from Gaia DR2 we also derive orbits in a realistic Milky-Way potential. We find that our previous radial-velocity selected LA candidates have substantial orbital angular momentum. The substantial amount of rotational component for these stars is in contrast with the near-polar Magellanic orbit, thus rendering these stars unlikely members of the LA. There are four large orbital-energy stars in our sample. The highest orbital-energy one has an age shorter than the time to disk crossing, with a birthplace z = 2.5 kpc and R GC ~ 28 kpc. Therefore, the origin of this star is uncertain. The remaining three stars have disk runaway origin with birthplaces between 12 and 25 kpc from the Galactic center. Also, the most energetic stars are more metal poor ([Mg/H] =-0.50 +/- 0.07) and with larger He scatter (sigma [He/H] = 0.72) than the inner disk ones ([Mg/H] = 0.12 +/- 0.36, sigma [He/H] = 0.15). While the former group's abundance is compatible with that of the Large Magellanic Cloud, it could also reflect the metallicity gradient of the MW disk and their runaway status via different runaway mechanisms.
Keywords: dept.phy; stars: abundances; stars: early-type; stars: kinematics and dynamics